1994
DOI: 10.1176/ajp.151.8.1209
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement impairment and schizotypal psychopathology

Abstract: Patients with schizotypal personality disorder demonstrate qualitatively poorer tracking than comparison groups, and the impaired tracking is associated with deficit-like symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In terms of eye-tracking dysfunction among individuals with schizotypic psychopathology, such deficits are clearly found among clinically defined schizotypes (e.g., Siever et al, 1994) and psychometrically identified schizotypes (O'Driscoll, Lenzenweger, & Holzman, 1998). Eye-tracking dysfunction has also been found to aggregate in the biological family members of patients with schizophrenia across numerous studies (Levy et al, 1993).…”
Section: Laboratory Studies Of Schizotypic Psychopathologymentioning
confidence: 99%
“…In terms of eye-tracking dysfunction among individuals with schizotypic psychopathology, such deficits are clearly found among clinically defined schizotypes (e.g., Siever et al, 1994) and psychometrically identified schizotypes (O'Driscoll, Lenzenweger, & Holzman, 1998). Eye-tracking dysfunction has also been found to aggregate in the biological family members of patients with schizophrenia across numerous studies (Levy et al, 1993).…”
Section: Laboratory Studies Of Schizotypic Psychopathologymentioning
confidence: 99%